TOURNAISIAN AGE OF GRANITOIDS FROM THE ODRA FAULT ZONE (SOUTHWESTERN POLAND): EQUIVALENT OF THE MID-GERMAN CRYSTALLINE HIGH? - Dörr W.; Żelaźniewicz A.; Bylina P.; Schastok Ja.; Franke W.; Haack U.; Kulicki C. (My University, 2006)
The Odra Fault Zone of southwestern Poland is a NW-trending horst marked by gravimetric and magnetic anomalies and composed of high- to low-grade metamorphic and igneous rocks which are only known from boreholes. This zone embraces a concealed border between Variscan internides and externides. It also contains an array of several I-type, metaluminous to peraluminous, high potassic granitoid bodies which intruded earlier metamorphosed rocks. Except for one case, they remain unfoliated and undeformed, and presumably play a role of stitching plutons at the suture between two obliquely colliding terranes. U–Pb TIMS dating of single zircons from one foliated and one unfoliated granitoid samples yielded identical concordant ages of 344±1 Ma (Tournaisian). They resemble a Pb–Pb age of 350±5 Ma obtained for S-type granitoids from the Luckau area further west in Germany, which is generally regarded as an eastern segment of the Mid-German Crystalline High. Carboniferous granitic intrusions in the high are generally younger (340–290 Ma). Correlations of the the Odra Fault Zone with the Mid-German Crystalline High appear plausible, but by no means certain and require further confirmation.
Keywords: ARMORICA; SAXOTHURINGIAN ZONE; SUDETES; TERRANE; U-PB DATING; WIELKOPOLSKA; ZIRCON; Tournaisian; Paleozoic::Carboniferous::Mississippian::Lower::Tournaisian; Палеозой::Каменноугольная::Нижний::Турнейский